The Role of Political Radio Talk Shows in Promoting Democracy and Freedom Rights in Uganda. A Case Study the Role of Rukiiko Radio Talk Show on 89.5 Voice of Kigezi in Promoting Democracy and Freedom Rights in Kabale District. - Joshua Niwaha (Uganda Christian University, 2024)
Abstract: This research investigates the role of political radio talk shows in promoting democracy and freedom rights within Uganda, focusing on a case study of the Rukiiko Radio Talk Show on 89.5 Voice of Kigezi in Kabale District. As Uganda's media landscape grapples with issues of censorship and political control, the study explores how local radio talk shows, particularly Rukiiko, contribute to democratic discourse and the protection of freedom rights. By analyzing listener engagement, content themes, and the impact on local political awareness and activism, this research aims to elucidate the ways in which such talk shows foster democratic participation and promote human rights at the grassroots level. Through a combination of qualitative interviews, content analysis, and audience surveys, the study assesses the effectiveness of Rukiiko in providing a platform for political debate, public accountability, and civic engagement in a context where traditional media freedoms are often restricted. The findings offer insights into the role of community radio in strengthening democratic values and advocating for freedom rights in a challenging political environment.
Undergraduate Research